Estimation of neopterin as a biomarker in biofluids of pre and post-menopausal women after initial periodontal therapy: A biochemical assay - Jammula Surya Prasanna; Chinta Sumadhura (Wolters Kluwer Medknow Publications, 2021)
Context: Periodontitis (PDD) is a chronic inflammatory condition by nature which destroys the surrounding tooth structures. Menopause (pre and post) worsens the inflammatory state. Biofluids could serve as sources of biomarkers that could diagnose or indicate the intensity and extent of both conditions. Aims: This study aimed to guestimate the various biofluids of neopterin (NP) levels in premenopause (pre-m) and postmenopausal (post-m) women with PDD after initial periodontal therapy (IPT). Settings and Design: This was an interventional cross-sectional study. Materials and Methods: Based on menstrual history, within the age range of 40-60 years, 30 female patients having PDD participated, who were grouped into pre-m and post-m, each group comprised 15 subjects. A biochemical test of NP levels was done at the initial and three months following IPT. Statistics used: Group comparisons and percentage decrement using independent sample t-test and paired t-test for intragroup comparison were done with the version 21, IBM SPSS software. Results: Intragroup NP analysis at different time points showed significant improvement. Intergroup comparison, however, has shown significant improvement in the premenopausal group (Group I) only. Conclusions: Reduced levels of NP were found in pre-m and post-m groups 3 months after IPT, inferring that IPT is a paragon in periodontal therapy and NP might be a good diagnostic marker to detect PDD.